Anniversary article: The practices of encouraging TESOL teachers to engage in reflective practice: An appraisal of recent research contributions. (March 2016) - Farrell, Thomas SC
Within the field of education, reflective practice has become a very popular concept within teacher education and development programs. The general consensus is that teachers who are encouraged to engage in reflective practice can gain new insight of their practice. There have been similar developments in the field of teaching English to speakers of other languages (TESOL), where the allure of reflective practice seems to have also been embraced as an important educational paradigm that should be supported in teacher education and development programs. However, we really do not know what research has been conducted on the practices that encourage TESOL teachers to participate in reflective practice. This article presents a review of recent research that has been published in academic journals over the past five years (2009–2014) on the practices that encourage TESOL teachers to reflect.